Beamforming in an annular duct with swirling flow - Sijtsma, P.; Brouwer, H.; Snellen, M. (AIAA, 2023)
The fan-stator stage of turbofan engines is one of the main regions of broadband noise generation. The trend of increasing bypass ratios will make fan-stator broadband noise even more significant, as jet noise will decrease and nacelles will become shorter, thus leaving less space for liners. Within the fan-stator stage there are several aerodynamic phenomena that can cause broadband noise. However, techniques for experimental identification and quantification (and thus classification) of these broadband noise sources are still immature. Beamforming using in-duct microphones is feasible, but a major challenge is the strong rotational component of the flow that needs to be accounted for in the steering vectors. This paper proposes a solution for that challenge, based on a fast ray tracing approach. With synthesized microphone array data, calculated with an approximate method for the Green’s function in a ducted swirling flow, it is demonstrated that detection of acoustic sources is possible.